TELAAH KURIKULUM MATA PELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Sari, Andi Putri; Hamzah, Rahma Ashari; Adawiyah, Warda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
Curriculum review is an in-depth and systematic analysis of curriculum elements such as objectives, materials, methods, and evaluation, to understand their effectiveness and implementation. This study aims to comprehensively review the Indonesian language curriculum in Elementary Schools (SD). The focus of the review includes the operational definition of the curriculum, main components (objectives, materials, methods, assessments), examples of implementation, implementation challenges, and the formulation of more relevant and effective development recommendations. Qualitative descriptive methods are used to explore the perceptions and experiences of stakeholders such as teachers, principals, and curriculum developers through document analysis, interviews, and teaching observations. The results of the review are expected to provide a clear picture of the strengths and weaknesses of the current curriculum, as well as data-based recommendations to improve the quality of curriculum design and implementation. The purpose of this study is to contribute significantly to the understanding of the Indonesian language curriculum in SD and become a basis for decision making to improve the quality of education, with the hope of producing a more effective curriculum in developing students' language competencies holistically.